Zimbabwean societal perceptions of the depiction of women in Matavire’s two love songs. - Makunganya, Abraham (Midlands State University, 2017)
The main purpose of this research was to establish the Zimbabwean societal perceptions of the depiction of women in Matavire’s two love songs. The researcher had to interview respondents to get their views on how Paul Matavire’s music depict women. A qualitative content analysis was used to gather data. The study showed that women are portrayed in various ways. They are subjected to naming, demeaning words, sexual objectifications and considered weak. It also emerged that while Paul Matvire sang for humour, their love issues raised in his songs were real. He therefore conscientised the society the rough singing real life situations and issues on gender inequality. It emerged that Paul Matavire, as perceived by interviewees, is highlighting the plight of women. Women are however strong and ready to defend their position despite the gender imbalances which militate against them. Patriarchy is blamed for this scenario. The study was guided by the theory of feminism as its analytical mental framework to assess the position of women in society. Finally, the music education and performance in an effort to create co-existentiality among women and men.